Atopic eczema and allergies: Practical relevance for diagnostic work-up - Prucha, Hanna; Chen, Wenchieh; Traidl-Hoffmann, Claudia; Todorova, Antonia; Akdis, Cezmi; Lauener, Roger; Ring, Johannes (Community Based Medical Journal, 2013)
Atopic eczema (AE) is a chronic relapsing skin disease mostly starting in childhood and often associated with allergic asthma and rhinoconjunctivitis. In the etiopathophysiology of atopic eczema skin barrier disturbance and immune deviation with a predominant Th2 response and IgE production are central. Allergy tests belong to the diagnostic work-up of AE patients, first in order to differentiate between the extrinsic (IgE-associated) from the intrinsic (non-IgE-associated) form of the disease. Essntially allergy tests are mandatory in order to find individual provocation factors for exacerbation or maintenance of eczema. These allergy tests include skin prick test (SPT), radio-allergo-sorbent test (RAST) for specific IgE antibodies against common allergens and APT. Since numerous AE patients suffer from contact allergy, therefore classical patch testing is mandatory. Although SPT and RAST have a quite high sensitivity, but the specificity of APT is much higher; revealing the fact that by APT the relevance of a certain allergen for the actual skin disease can be confidently evaluated. In suspected food allergy the gold standard is still double-blind placebo-controlled oral provocation test which should be performed in a symptom-free period after an individual elimination diet and under emergency conditions, since anaphylactic reactions may occur in AE patients. In the long-term management of AE patients educational programs eczema school have proved to be helpful. DOI: http://dx.doi.org/10.3329/cbmj.v2i2.16693 Community Based Medical Journal 2013 July: Vol.02 No 02: 15-24